(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper is developed to shed light on the old perspective that language is never enough to grasp the feeling, and no matter how much we express, there is always something ineffable about it. A concept is an umbrella term that can be described in a number of ways. In section 1, I discussed different notions of concepts. Section 2 will address the ineffability of the phenomenal mental states, specifically focusing on Wittgenstein’s (1953/2009) notion of the use of words and private language. In section 3, I will shed light on pure phenomenal concepts (Chalmers 2010). Finally, I will show why the language categories cannot adequately capture the phenomenal concepts. I will conclude that language is never enough to grasp what one feels.